Brain functional network topology and connectivity in primary blepharospasm - Yao, Xin-Xin; Li, Hua-Liang; Wang, Shu; Gu, Si-Yu; Hu, Jian-Bin; Li, Wen-Hui; Pan, Ping-Lei (Frontiers in Systems Neuroscience, 2025)
BackgroundThe pathophysiology of primary blepharospasm (BSP) remains incompletely understood. This study aimed to characterize whole-brain functional network topology in treatment-naive BSP patients.MethodsThirty-nine treatment-naive BSP patients and 39 matched healthy controls (HCs) underwent resting-state fMRI. Graph theoretical analysis was applied to assess global and nodal network metrics. Network-Based Statistics (NBS) identified subnetworks with altered functional connectivity (FC). Correlations between network metrics and clinical variables [Jankovic Rating Scale (JRS), illness duration] were explored.ResultsCompared to HCs, BSP patients exhibited significantly lower local efficiency [p = 0.0002, false discovery rate (FDR) corrected], while global efficiency, characteristic path length, clustering coefficient, normalized clustering coefficient, normalized characteristic path length, or small-worldness were preserved (all p > 0.05, FDR corrected). Nodal analysis revealed decreased efficiency/degree in the bilateral thalamus and left supplementary motor area, and increased efficiency/degree in the bilateral precentral gyri, right postcentral gyrus, and left insula (all p < 0.05, FDR corrected). NBS identified subnetworks with altered FC across sensorimotor, limbic-subcortical, frontoparietal, and default mode networks, featuring both hyper- and hypo-connectivity (p < 0.05, NBS-corrected). Notably, left thalamic efficiency negatively correlated with illness duration (r = −0.481, p = 0.0019), and right precentral gyrus efficiency positively correlated with JRS total score (r = 0.395, p = 0.0129).ConclusionBSP is characterized by complex functional network disruptions, including impaired local information processing, altered nodal importance in key motor and relay hubs, and widespread connectivity changes. These findings reinforce BSP as a network disorder. These network alterations may serve as objective markers for disease progression and could guide the development of targeted neuromodulation therapies.